From African pipe dreams to incremental sanitation improvements through experimentation - (:unkn) unknown (My University, 2023)
In February 2023 the team of the research project OVERDUE – tackling the sanitation taboo across urban Africa embarked on a knowledge exchange visit to India to learn from the Indian Institute for Human Settlement’s Tamil Nadu Urban Sanitation Support Programme (TNUSSP). The first days included two field visits in Chennai, one to a public/community toilet (PT/CT) in Kottivakam and the other to one of the city’s 13 sewage treatment plants (STP), Sholinganallur. In this blog we reflect on this knowledge exchange and what struck us the most.
Keywords: African Research